Spinal drain for aortic aneurysm repairs: tool or toy?. Issue 1 (14th February 2023) - Bastug, Nicholas; Worrall, Eric; Webb, Laura; Larson, Robert
Abstract : Purpose of review: Spinal cord injury (SCI) is one of the biggest complications in open and endovascular aortic repairs. Historically, cerebrospinal fluid drains (CSFD) have been one of the most effective modalities in reducing SCI and one of the most studied. CSFD placement also carries its' own set of procedural risks. This editorial intends to evaluate recent literature to determine whether CSFDs remain a valuable tool in aortic repair. Recent findings: As the surgical management of thoracic aortic aneurysms has evolved, there has been an increasing number of endovascular repairs. Current recommendations emphasize prophylactic CSFD placement in endovascular repair cases deemed 'high risk.' However, several meta-analyses differ on whether prophylactic CSFD placement reduced the risk of SCI. The incidence of SCI decreased between 2014 and 2018, despite a similar rate of prophylactic CSFD placement suggesting other techniques are being performed and may be effective in spinal cord protection as well. Summary: There has been conflicting data on whether CSFDs have a role in reducing the risk of SCI in endovascular aortic repair. Some studies suggest that there is no benefit to placement while others suggest that routine prophylactic drains should be placed for all endovascular cases. Despite this, efforts have been made to selectively place CSFDs in those patients deemed at 'high risk' for SCI. CSFDs also remain a part of rescue treatment for postoperative SCI. This suggests that CSFDs continue to be a valuable tool that we need to better comprehend. Future research is necessary to better understand how patient risk factors can be balanced with perioperative management to help identify patients who may benefit from CSFD placement.